2016
DOI: 10.1016/j.bjm.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Azole resistance in Candida spp. isolated from Catú Lake, Ceará, Brazil: an efflux-pump-mediated mechanism

Abstract: Since, there is no study reporting the mechanism of azole resistance among yeasts isolated from aquatic environments; the present study aims to investigate the occurrence of antifungal resistance among yeasts isolated from an aquatic environment, and assess the efflux-pump activity of the azole-resistant strains to better understand the mechanism of resistance for this group of drugs. For this purpose, monthly water and sediment samples were collected from Catú Lake, Ceará, Brazil, from March 2011 to February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…It has also been reported that azole‐resistant Candida isolates have been found in lake water and in a porcupine in Brazil. The resistance were mediated by efflux pumps . Whether these findings have implications for human infection is unknown as our study was not designed to reveal associations between agricultural azoles and candidaemia or Candida resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that azole‐resistant Candida isolates have been found in lake water and in a porcupine in Brazil. The resistance were mediated by efflux pumps . Whether these findings have implications for human infection is unknown as our study was not designed to reveal associations between agricultural azoles and candidaemia or Candida resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance were mediated by efflux pumps. 30,31 Whether these findings have implications for human infection is unknown as our study was not designed to reveal associations between agricultural azoles and candidaemia or Candida resistance. Another study design is needed to discover any association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the authors observed that yeast derived from freshwater lakes with resistance to fluconazole and itraconazole had the activity of its efflux pumps inhibited by the addition of promethazine and haloperidol. MIC tests performed after this test resulted in a reversal of the azole-resistant An Acad Bras Cienc 2019) 91(1e20170369 9 | 12 phenotype, indicating a direct involvement of the efflux pumps in the drug sensitivity of yeast (Brilhante et al 2016). The sequencing of isolates was performed in this study to identify samples with resistance to amphotericin B, resulting in seven isolates belonging to the genus Candida.…”
Section: Discussionmentioning
confidence: 98%
“…The hypothesis that antifungal resistance of yeasts could be achieved through exposure to nonspecific compounds derived from various sources of pollution has been reinforced in a recent study published by Brilhante et al (2016). In their work, the authors observed that yeast derived from freshwater lakes with resistance to fluconazole and itraconazole had the activity of its efflux pumps inhibited by the addition of promethazine and haloperidol.…”
Section: Discussionmentioning
confidence: 99%